A landscape of design: interaction, interpretation and the development of experimental expressive interfaces - Chamberlain, Alan; Bødker, Mads; De Roure, David; Willcox, Pip; Emsley, Iain; Malizia, Alessio (Springer International, 2018)
This paper presents the initial research insights of an ongoing research project that focuses upon understanding the role of landscape, its use as a resource for designing interfaces for musical expression, and as a tool for leveraging ethnographic understandings about space, place, design and musical expression. We briefly discuss the emerging research and reasoning behind our approach, the site that we are focusing on, our participatory methodology and conceptual designs. This innovative research is envisaged as something that can engage and interest the conference participants, encourage debate and act as an exploratory platform, which will in turn inform our research, practice and design.